2008
DOI: 10.1007/s10350-007-9098-y
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Anal Cytologic Abnormalities in a French Referral Population: A Prospective Study with Special Emphasis on HIV, HPV, and Smoking

Abstract: This work confirms that the frequency of low-grade squamous intraepithelial lesion is raised in HIV-seropositive males and also where there is a history of condyloma, which corroborates the necessity for regular monitoring and screening of these patients at risk. This study also suggests that the use of tobacco is associated with anal cytologic abnormalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0
3

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 22 publications
3
7
0
3
Order By: Relevance
“…In fact, in our study of HIV‐infected men without a known history of anal condylomata, having anal condylomata was associated with a higher prevalence of high‐grade cytological lesions in the anal canal. This finding is in agreement with that of another study . Furthermore, results from a study of a large urban population of MSM with condylomata requiring surgical excision showed that these patients had a high frequency of occult high‐grade anal intraepithelial neoplasia or anal squamous cell cancer .…”
Section: Discussionsupporting
confidence: 92%
“…In fact, in our study of HIV‐infected men without a known history of anal condylomata, having anal condylomata was associated with a higher prevalence of high‐grade cytological lesions in the anal canal. This finding is in agreement with that of another study . Furthermore, results from a study of a large urban population of MSM with condylomata requiring surgical excision showed that these patients had a high frequency of occult high‐grade anal intraepithelial neoplasia or anal squamous cell cancer .…”
Section: Discussionsupporting
confidence: 92%
“…In addition, other behavioral factors such as smoking, which was found to be associated with low‐grade squamous intraepithelial lesions in this study as in previous studies [Etienney et al, ; Chaves, 2012], could play a role in the development of anal carcinoma [Daling et al, ; Tolstrup et al, ; Kojic et al, ].…”
Section: Discussionsupporting
confidence: 81%
“…41 Cigarette smoking is linked to anal cancer and cytologic abnormalities. 42,43 There is some protection against AIN in patients with HIV who have high CD4+ T helper cell counts and controlled viral loads. 25 Male circumcision reduces penile oncogenic HPV infection, markedly reduces the risk of penile cancer and reduces the risk of cervical cancer in female partners.…”
Section: Is Anal Cancer Preventable?mentioning
confidence: 99%